Erythrocyte membrane-encapsulated SZF nanocomposites for hyperuricemia therapy - Liu, Weiwei; Guan, Xin; Wang, Luobing; Zhang, Chengjie; Shen, Boyi; Zeng, Yuke; Li, Dongdong; Pu, Guangjin; Hu, Jing; Gao, Jiandong (Frontiers in Immunology, 2026)
IntroductionHyperuricemia is a prevalent metabolic disorder primarily induced by purine dysregulation. Current therapies face limitations due to systemic side effects and inadequate efficacy, necessitating novel treatment strategies.MethodsIn this study, a biomimetic nanodrug, SZF@PDA‑RM, was synthesized by hybridizing the traditional medicine Shizhifang (SZF) with polydopamine (PDA), followed by erythrocyte membrane coating. Its physicochemical properties and reactive oxygen species (ROS)-responsive release were characterized. In vitro, a hyperuricemia cell model using uric acid (UA)-stimulated renal tubular cells (NRK‑52E) assessed cellular uptake, biosafety, ROS scavenging, and mitochondrial protection. Molecular mechanisms were probed via immunofluorescence, western blot, and inhibitor studies. In vivo efficacy and safety were evaluated in a hyperuricemic mouse model by measuring serum/urinary biomarkers, renal histopathology, and tissue ROS.ResultsThe synthesized SZF@PDA‑RM exhibited a spherical morphology, demonstrating good stability and significant ROS-responsive drug release properties. The erythrocyte membrane coating effectively prolonged its systemic circulation. In the cellular model, SZF@PDA‑RM efficiently reduced UA-induced intracellular and mitochondrial ROS levels, restored mitochondrial membrane potential, mitigated mtDNA damage, and inhibited the activation of the NLRP3 inflammasome and the expression of downstream cytokines. Mechanistically, the nanoformulation negatively regulated mitochondrial ROS generation by promoting the interaction between SHP2 and ANT1, an effect that was reversed by SHP2 inhibitors. In the animal model, treatment with SZF@PDA‑RM significantly lowered serum uric acid, creatinine, and multiple urinary renal injury biomarkers in hyperuricemic mice. It also alleviated renal inflammatory infiltration and fibrosis, cleared renal tissue ROS, and showed no systemic toxicity.ConclusionThe erythrocyte membrane-camouflaged SZF@PDA‑RM nanocomposite achieves long circulation and targeted delivery. It exerts a multi-target synergistic therapeutic effect by directly scavenging ROS, maintaining mitochondrial homeostasis via the SHP2/ANT1 pathway, and inhibiting NLRP3-mediated inflammation, thereby effectively improving uric acid metabolism and alleviating renal injury.